PENGEMBANGAN MULTIMEDIA PEMBELAJARAN UNTUK MENGENALKAN KONSEP BILANGAN PADA ANAK TAMAN KANAK-KANAK GLOBAL MAJU KHATULISTIWA - Julia, Julia; Fadillah, Fadillah; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractAmong the basic things that become difficult to recognize the concept of numbers due to the introduction of the concept of the number 1-10 for children aged 4-5 years is still not maximal so difficult to understand by children, thus requiring learning media in the form of multimedia learning. This study aims to produce multimedia design learning in recognizing the concept of numbers and to describe the results of children's learning in TK Global Maju Khatulistiwa. This research develops multimedia by using the development stage of Borg and Gall, with the subject of research is kindergarten A children amounting to 16 people. Stages of multimedia learning development that is done is research and information collecting, planing, Develop preliminary form of product, main field testing, operational product revision, and Final product revision. Data obtained through expert validation test, observation, interview, and documentary. Furthermore, data analysis of expert validation, observation, interview and documentation were performed. Result of research can give influence to result of learning, this matter seen from pretest that is before using multimedia average 4,98 which experienced difference of result posstest average equal to 8,68. The results of study can also be seen from the test results 2 paired samples showing the significance value of t statistics  >  t table (14.81 > 1.74) means that there is influence of learning results using multimedia learning in introducing the concept of numbers.Keywords: development, multimedia learning, concept number